ePublishing: Challenges & Opportunities - Siddiqui, Atiq (2004)
The recent explosive development in information technology (IT) is challenging the traditional forms of communication and publishing. The new IT tools open a new kind of research practice that is impossible several years back. Journal publication is at a crossroad. Academics and Publishing houses have tough choices to make: either leave the journal system as is and face possible erosions or adopt and exploit the opportunities IT is providing. It seems academics are adopting the latter choice. Many publishers are adopting e-publication and more adopting the parallel publishing. However switching from traditional to electronic publishing raises a number of opportunities and challenges to the journal systems. The opportunities are: ease of access, fast response to authors, cost savings, large storage capabilities, fluidity of electronic document etc. Challenges include: Quality control of published material, preserving the peer review system, preserving the Intellectual property. The purpose of this paper is to review experiences in electronic journal publication and examine the opportunities and challenges facing the journal system. It will also attempt to set requirements and standards for e-journal publication.